A venom dark and sweet - Lin, Judy I. (Book of tea, 2022)
A great evil has come to the kingdom of Dàxi. The Banished Prince has returned to seize power, his rise to the dragon throne aided by the mass poisonings that have kept the people bound in fear and distrust. Ning, a young but powerful shénnóng-shi—a wielder of magic using the ancient and delicate art of tea-making—has escorted Princess Zhen into exile. Joining them is the princess' loyal bodyguard, Ruyi, and Ning's newly healed sister, Shu. Together the four young women travel throughout the kingdom in search of allies to help oust the invaders and take back Zhen's rightful throne. But the golden serpent still haunts Ning's nightmares with visions of war and bloodshed. An evil far more ancient than the petty conflicts of men has awoken, and all the magic in the land may not be enough to stop it from consuming the world...
Keywords: Ning : (fiktiivinen hahmo); Zhen : (fiktiivinen hahmo); magia; valtataistelu; tee; maanpako; vallankäyttö; prinsessat; siskot; hyvän ja pahan välinen taistelu